VALUASI SAHAM MENGGUNAKAN METODE PRICE TO EARNING RATIO PADA SAHAM SEKTOR PERTAMBANGAN YANG TERGABUNG DALAM IDX HIGH DEVIDEN 20 TAHUN 2019-2020 - Risqi Perdana; Juanita Horman (INTAN Jurnal Penelitian Tambang, 2022)
Stock valuation is an assessment of the fair price of a stock. Stock valuation is carried out to anticipate potential losses that will be received by investors. This study aims to determine the fair price of the stock and choose the appropriate stock to be used as an investment choice in the IDX High Devidend 20 Index stock. Stock price valuation is measured using the Price Earning Ratio (PER) approach. In conclusion, from the stock valuation results, it can be seen that ADRO, ITMG, and PTBA shares in 2019 were undervalued or cheap so the investment decision that can be taken is to buy shares in that year. In 2020 stocks with the code ADRO, ITMG, and PTBA are also still classified as undervalued so the investment decision that can be taken is to buy shares